ChemInform Abstract: Iron‐Catalyzed Reduction of Olefins Using a Borohydride Reagent. Issue 32 (18th July 2013) - Carter, Tom S.; Guiet, Lea; Frank, Dominik J.; West, James; Thomas, Stephen P.
Abstract Excellent yields are observed for the aliphatic and aromatic terminal alkenes.